A comparative analysis of the cytocompatibility, protein adsorption, osteogenic and angiogenic properties of the 45S5- and S53P4-bioactive glass compositions - Westhauser, Fabian; Arango-Ospina, Marcela; Hupa, Leena; Renkawitz, Tobias; Boccaccini, Aldo R.; Kunisch, Elke (Biomedical materials, 2024)
Despite their long history of application in orthopedics, the osteogenic and angiogenic properties as well as the cytocompatibility and protein adsorption of the 45S5- (in wt%: 45.0 SiO2, 24.5 Na2O, 24.5 CaO, 6.0 P2O5) and S53P4- (in wt%: 53.0 SiO2, 23.0 Na2O, 20.0 CaO, 4.0 P2O5) bioactive glass (BG) compositions have not yet been directly compared in one and the same experimental setting. In this study, the influence of morphologically equal granules of both BGs on proliferation, viability, osteogenic differentiation and angiogenic response of human bone-marrow-derived mesenchymal stromal cells (BMSCs) was assessed. Furthermore, their impact on vascular tube formation and adsorption of relevant proteins was evaluated. Both BGs showed excellent cytocompatibility and stimulated osteogenic differentiation of BMSCs. The 45S5-BG showed enhanced stimulation of bone morphogenic protein 2 (BMP2) gene expression and protein production compared to S53P4-BG. While gene expression and protein production of vascular endothelial growth factor (VEGF) were stimulated, both BGs had only limited influence on tubular network formation. 45S5-BG adsorbed a higher portion of proteins, namely BMP2 and VEGF, on its surface. In conclusion, both BGs show favorable properties with slight advantages for 45S5-BG. Since protein adsorption on BG surfaces is important for their biological performance, the composition of the proteome formed by osteogenic cells cultured on BGs should be analyzed in order to gain a deeper understanding of the mechanisms that are responsible for BG-mediated stimulation of osteogenic differentiation.
Gesehen am 07.06.2024